Prospect of the Fifth-Generation Mobile Communication System - Jie Shen (Dianxin kexue)
EU, China,South Korea and other regions and countries have set up group to study the fifth-generation mobile communications, proposed technical objectives and research directions. The fifth generation mobile communications will provide faster access speeds, wider bandwidth, more flexible configuration networking. Three aspects of the fifth generation mobile communication systems, i.e. technology, networking, application were studied, and some new research directions, new forms of self-organizing network architecture and future application prospects were presented. 5G mobile communications in China will provide broad opportunities to industry upgrade.